W/O/W Emulsions Formula of Bacteriophages ϕPT1b As a Fruit Wash to Inhibit Pathogenic Escherichia coli Contamination - Icha Khairunnisa; Erlia Narulita; Lina Winarti; Riska Ayu Febrianti; Kuswati Kuswati; Ria Yulian (Sanata Dharma University, 2025)
Pathogenic Escherichia coli infect fruit through irrigation contaminated water. Bacteriophage ϕPT1b has ability to infect E. coli and act as food security. Bacteriophage formulations as emulsion preparations increase the efficiency of application and the stability of long-term storage, one of it is W/O/W emulsions. The objective of this study was to examine the effect of cremophor RH 40, span 80 and their interaction on viscosity, droplet size and inhibition of bacteriophage ϕPT1b W/O/W emulsions against pathogenic E. coli. Factorial design method was used to get the optimum formula. The results showed that the cremophor RH 40, span 80, and their interactions increased the viscosity response, decreased the emulsion droplet size, and increased the inhibition against E. coli. FB is the optimum formula for ϕPT1b W/O/W emulsions which has 1% cremophor RH 40 and 4.5% span 80. The formula produced a viscosity of 29 dPas, an average emulsion droplet diameter size of 10.483, and an inhibition against E. coli of 8.65 m. The desirability index value of 0.905 indicates that FB meets 90.5% of the specified criteria.